1996
DOI: 10.1046/j.1464-410x.1996.09310.x
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cancer in various population groups in the greater Durban area of KwaZulu‐Natal, South Africa

Abstract: In African patients, endemic Schistosomiasis appears to be related to a high incidence of not only squamous cell carcinoma, but also undifferentiated tumours and adenocarcinoma of the bladder. The effective management of squamous cell carcinoma of the bladder in African patients will depend on the eradication of Schistosomiasis and the early detection of bladder cancer at a stage when it may still be cured by radical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 1 publication
0
22
0
1
Order By: Relevance
“…The mass being usually >3 cm in size at first presentation. [313233] The SCC is also muscle invasive in 80% of cases at the time at first presentation. [34] In contrast, TCC tends to be multifocal small and papillary like with little or no muscle invasion at first presentation.…”
Section: Discussionmentioning
confidence: 99%
“…The mass being usually >3 cm in size at first presentation. [313233] The SCC is also muscle invasive in 80% of cases at the time at first presentation. [34] In contrast, TCC tends to be multifocal small and papillary like with little or no muscle invasion at first presentation.…”
Section: Discussionmentioning
confidence: 99%
“… 16,17 This parasite is presumed to cause cancer by invoking chronic inflammation and interfering with the metabolism of cigarette smoke‐related bladder mutagens. Interestingly, most cancers caused by schistosomiasis are squamous cell in origin and appear in younger patients 18,19 …”
Section: Risk Factors For Bladder Cancermentioning
confidence: 99%
“…Its incidence in whites seems lower than in blacks even in the presence of the same environmental agents. Groeneveld et al [1]reported the incidence of the different histotypes of bladder cancer in various races living in the same region of South Africa. Squamous cell carcinoma represented 53% of all bladder tumors of the African patients but only 2% of the Caucasians.…”
Section: Introductionmentioning
confidence: 99%